New Zealand prison interior architecture in the 1890s - McCarthy, Christine (Architectural History Aotearoa, 2023)
Two large New Zealand prisons opened in the 1890s: Dunedin Gaol (1895-98), designed by John Campbell, and Mount Cook Gaol (1882-97, dem 1925), designed by Pierre Finch Martineau Burrows. While Burrows had designed Mount Cook (and its sibling at Mount Eden, which was reputedly modelled on a Malta prison and colonial Blue Books) it would be Dunedin Gaol’s architect, John Campbell, who would supervise the building through to completion. The two designs are very different - Dunedin having a courtyard, with echoes of Scotland Yard in London, and Mount Cook being a radial plan, the antecedent of which Newbold states to be Pentonville (London 1840-42). This paper considers the interiors of these prisons and the reasons for their differences.